Efektivitas Penggunaan Media Video Pembelajaran pada Mata Pelajaran IPA di Kelas 5A SD Inpres BTN IKIP 1 - Malliha Muthia Azka (Edutechno : Educational Technology Journal, 2026)
This study aims to evaluate the effectiveness of using instructional video media in the teaching and learning process for the Natural Sciences (IPA) subject in grade 5A at SD Inpres BTN IKIP 1. The background of this study is driven by the importance of visual media in bridging students' understanding of abstract science concepts, along with the need to enhance students' learning motivation and enthusiasm in the classroom. This study employs a quantitative descriptive method through a direct observation approach conducted by the researcher. Data were collected using an observation sheet that encompasses seven main indicators of effectiveness: speed of material comprehension, achievement of learning objectives, ability to answer reflection questions, increase in enthusiasm and motivation, concretization of abstract visualizations, student memory retention, and short assignment results. The results indicated that the video media obtained a total observation score of 24 out of a maximum score of 28, or an effectiveness percentage of 85.7%, categorized as "Very Effective". The highest level of effectiveness was observed in the indicators of increased student enthusiasm, ability to answer reflection questions, and visualization of concrete concepts, each of which achieved the maximum score. In conclusion, the use of video media shows a high indication of effectiveness when integrated into the grade 5A Natural Sciences learning process. Based on the observation results, this media is considered capable of supporting enhanced visual appeal, motivating students, and facilitating their cognitive understanding of the learning materials.